Axially Symmetric Bulk Viscous Cosmological Model in F(R, T) Theory of Gravity. Issue 1 (2nd January 2021) - Avchar, G.R.; Golechha, D.R.; Tade, S.D.
Abstract: In this paper, axially symmetric space-time in presence of perfect fluid with viscosity has been considered and studied within the framework of F ( R, T ) theory of gravity proposed by (Harko et al. [14]). The solutions of the field equations axe evaluated by assuming the proportionality of expansion ( θ ) to the shear scalar (σ). The physical and kinematical aspects of the model have also been discussed.